2014
DOI: 10.3389/fmicb.2014.00077
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of CheA3 in Desulfovibrio vulgaris Hildenborough motility

Abstract: Sulfate-reducing bacteria such as Desulfovibrio vulgaris Hildenborough are often found in environments with limiting growth nutrients. Using lactate as the electron donor and carbon source, and sulfate as the electron acceptor, wild type D. vulgaris shows motility on soft agar plates. We evaluated this phenotype with mutants resulting from insertional inactivation of genes potentially related to motility. Our study revealed that the cheA3 (DVU2072) kinase mutant was impaired in the ability to form motility hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…coli strain J-2561 containing a 5-kb (pBbS5c) plasmid was prepared using cells grown to an optical density (at 600 nm) of 1. Desulfovibrio was grown in LS4D supplemented with 0.1% (wt/vol) yeast extract (43) while E. coli was grown in LB medium.…”
Section: Methodsmentioning
confidence: 99%
“…coli strain J-2561 containing a 5-kb (pBbS5c) plasmid was prepared using cells grown to an optical density (at 600 nm) of 1. Desulfovibrio was grown in LS4D supplemented with 0.1% (wt/vol) yeast extract (43) while E. coli was grown in LB medium.…”
Section: Methodsmentioning
confidence: 99%
“…2 & Table S6). Additionally, the che operon structure in ULRT4_3.bins.101 was the same as that of cheA3 in D. vulgaris ( Figure S7), suggesting it had the ability to sense electron acceptors like sulfate and lactate [60].…”
Section: Mcp System Of Srmsmentioning
confidence: 84%
“…5). It was reported that Dv H forms motility halos on solid media that are mediated by flagella-related mechanisms via the CheA3 histidine kinase (37). This indicated that Dv H had increased motility or surface attachment in the anodic chamber.…”
Section: Discussionmentioning
confidence: 99%
“…A deletion mutant Dv H JWT716 was used in this study, which lacks the type 1 secretion system’s ABC transporter protein resulting in a deficiency in biofilm formation (36). The deletion mutant Dv H JW3422 strain, which is a deletion of the gene coding for the pilin protein (DVU2116), was constructed using the same marker replacement plasmid and method as strain JW9003 from a previous study (37). The plasmid for deleting DVU2116 and replacing with a kanamycin resistance gene was transformed into Dv H JWT700 and deletion was confirmed by Southern Blot.…”
Section: Methodsmentioning
confidence: 99%